PENDAMPINGAN TADARRUS AL-QUR'AN METODE 5T KUNCI PENINGKATAN MOTIVASI DAN INTERAKSI SANTRI TAHFIDZ LTIQ AS-SYIFA DENGAN AL-QUR'AN - Khoirul Muhtadin; Asep Warnudin (Jurnal Pengabdian Masyarakat (Bisma), 2025)
This community service activity addresses the prevalent issue in tahfidz programs in Indonesia, where memorization often overshadows understanding, implementation, and character development. The study aims to enhance motivation and deep interaction with the Al-Qur'an among 110 new tahfidz students (80 female, 30 male) at LTIQ As-Syifa, focusing on Surah Fatir verse 32. Utilizing an interactive lecture model, the "5T Method" (Tamhid, Tilawah, Tafsir, Tadabbur, Tazkiyah) was implemented. Pre-test results indicated a lack of prior exposure to the 5T method, low intrinsic motivation, limited tafsir understanding, and no prior tazkiyah practice. Post-test findings demonstrated that all students mastered the 5T technique, experienced profound motivational correction, gained accessible tafsir understanding, and developed enthusiasm for practical tadabbur and tazkiyah. This signifies the method's effectiveness in fostering comprehensive engagement with the Qur'an, suggesting its frequent integration in tahfidz programs to cultivate holistic memorizers.